Ve' Licious Enterprise / Cynthia Elizabeth Duis... [et al.] - Duis, Cynthia Elizabeth; Vincent, Jessheila; Michael, Marounickley; Daraim, Netellyne; John Baptist, Nora (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA, 2009)
The business that we would like to open up is local home-made ice-cream business which we named Ve' Licious Enterprise. Ve' Licious Enterprise will be located at the 2nd Level Lot G of 1 Borneo Hypermall Alamesra, Kota Kinabalu. We choose to open up an ice-cream business because even though ice-cream is not something that we consume all the time, but the demands still exist and based from our conducted research, we found that there are nine ice-cream lovers among ten respondents. In our business, we are introducing fruit and vegetable flavoured ice-cream to the public. The idea of selling fruit and vegetable flavoured ice-cream is not entirely new because such idea has already existed but there's only one similar business in Sabah, which is Veda Blu that based in lnanam with four established branches throughout Sabah. We are aiming to introduce a much affordable than our competitors and healthy local home-made ice-cream to the Sabah people and we believe that with sufficient promotional activities due time, people will be aware of our product existence and enjoys consuming our product. And when our business is going well, only then we will consider opening up new branch at another chosen location in Sabah. Our business concept is that we open up our ice-cream booth and only sell our ice-cream in a wafer cone for environmental reason such as to help in reducing the global usage of the harmful Styrofoam and plastics container because these items is not easily recycled and unbiodegradable as compared to wafer cone which you can consume along with the ice-cream.